Development and validation of a self-assessment-based instrument to measure elementary school students' attitudes in online learning - Setiawan, Ari; Cendana, Wiputra; Ayres, Mark; Yuldashev, Azim Abdurakhmanovich; Setyawati, Sri Panca (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2023)
Online learning during the COVID-19 pandemic makes it difficult for teachers to assess student learning attitudes. Limited availability of instruments to measure attitudes of students when they are engaged in online learning leads to difficulty of teachers to conduct appropriate assessments on that measure. The current study, therefore, mainly was intended to produce a self-assessment-based instrument that is feasible to use to measure students' attitudes in online learning. In order to produce such instrument, we used developmental research method by following steps in the instrument design that is proposed by McCoach, Gable, and Madura. Furthermore, in order to provide feasibility of our instrument, we provided evidence of content validity through experts' judgment data as well as evidence of construct validity with confirmatory factor analysis (CFA) and reliability estimation with Cronbach's Î± through a limited trial and an expanded trial using response data of sixth graders of elementary school engaged in online learning. Our study has produced a self-assessment-based instrument that uses a summated rating scale and is composed of six components (i.e., honest, disciplined, responsible, polite, caring, and self-confident) and 24 items that have demonstrated evidence of content validity, stable factor structure, and high reliability estimates.